Age at menarche and risk of type 2 diabetes among African-American and white women in the Atherosclerosis Risk in Communities (ARIC) study - Dreyfus, J.; Lutsey, P.; Huxley, Rachel; Pankow, J.; Selvin, E.; Fernández-Rhodes, L.; Franceschini, N.; Demerath, E. (2012)
Aims/hypothesis: We examined race differences in the association between age at menarche and type 2 diabetes before and after adjustment for adiposity. Methods: We analysed baseline and 9-year follow-up data from 8,491 women (n = 2,505 African-American, mean age 53.3 years; n = 5,986 white, mean age 54.0 years) in the Atherosclerosis Risk in Communities (ARIC) study. Stratifying by race, we used logistic regression to estimate the OR for prevalent diabetes at baseline, and Cox proportional hazard models to estimate the HR for incident diabetes over follow-up according to age at menarche category (8-11, 12, 13, 14 and 15-18 years). Results: Adjusting for age and centre, we found that early age at menarche (8-11 vs 13 years) was associated with diabetes for white, but not African-American women in both the prevalent (white OR 1.72, 95% CI 1.32, 2.25; African-American OR 1.13, 95% CI 0.84, 1.51; interaction p = 0.043) and incident models (white HR 1.43, 95% CI 1.08, 1.89; African-American HR 1.20, 95% CI 0.87, 1.67; interaction p = 0.527). Adjustment for adiposity and lifestyle confounders attenuated associations for prevalent (white OR 1.41, 95% CI 1.05, 1.89; African-American OR 0.94, 95% CI 0.68, 1.30; interaction p = 0.093) and incident diabetes (white HR 1.22, 95% CI 0.92, 1.63; African-American HR 1.11, 95% CI 0.80, 1.56; interaction p = 0.554). Conclusions/interpretation: Early menarche was associated with type 2 diabetes in white women, and adulthood adiposity attenuated the relationship. We did not find a similar association in African-American women. Our findings suggest that there may be race/ethnic differences in the influence of developmental factors in the aetiology of type 2 diabetes, which merit further investigation. © 2012 Springer-Verlag.